(untitled) (CIPEEX, 2025)
The objective of this study is to compare the effects of ten sessions of treadmill training performed after 20 minutes of rTMS application on the active primary motor cortex and placebo in the domain of Activity (walking, functional mobility, functional balance, and gross motor function) and Participation of the ICF in children with spastic CP. This is a randomized, placebo-controlled, double-blind clinical trial involving 34 children diagnosed with spastic CP. Participants will be assessed one week before, one week and one month after the end of the intervention using the Modified Ashworth Scale, Tardieu Scale, Muscle Strength Assessment, motor evoked potential, Timed Up and Go, Walk Test, Berg Balance Scale, Gross Motor Function Measurement, and Participation and Environment Measure - Children and Youth. The experimental group will perform gait training on a treadmill after active rTMS application to the primary motor cortex, and the control group will perform gait training after placebo rTMS application. The intervention will involve ten intervention sessions, with a frequency of five sessions per week, carried out over two consecutive weeks and lasting 40 minutes each (20 minutes of rTMS and 20 minutes of treadmill training). Considering the potential effect of rTMS on the primary motor cortex, the intervention is expected to increase the effect size of gait training in children with CP.